Dynamic Analysis of Determinants of Financial Inclusion in Cameroon - Gautier, Tchoffo Tameko; Luc, Nembot Ndeffo; Djimoudjiel, Djekonbe (European Scientific Journal, ESJ, 2020)
The aim of this study is to identify the determinants of financial inclusion in Cameroon between 2011 and 2014. The study uses the maximum likelihood method applied to a logistic regression model. The results shows that the main determinants of financial inclusion in Cameroon are education and income. However, the education variable negatively influences all indicators of financial inclusion. While, income positively affects all indicators of financial inclusion over the two periods apart from the type of credit to which it is negatively correlated in 2011. The policy implication of this study is that the State in its institutional, legal and regulatory framework policies, set up a strategy to encourage financial education so as to draw the attention of all the population to basic foundations on the value of money, the functioning of the financial sector, the proper use of credit and mobile accounts.